The Influence of Leadership Style and Work Motivation on Employee Performance at Mutiara Cikutra Main Clinic - Atika Endras Yuspitasari; Muji Rahayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of leadership style and work motivation on employee performance. The research population consists of employees of Klinik Utama Mutiara Bandung. A quantitative associative approach was employed to measure the relationships and effects among variables numerically. The sample included 50 respondents, determined using the Slovin formula with a 5 percent margin of error, comprising medical staff, paramedics, and administrative personnel. The research instrument was a questionnaire based on a five-point Likert scale, developed using indicators derived from relevant literature. Data were analyzed with SPSS software through descriptive statistics, validity and reliability testing, and simple linear regression analysis. The results revealed that, partially, leadership style had no significant effect on employee performance, while work motivation showed a positive and significant impact. However, when tested simultaneously, leadership style and work motivation together demonstrated a significant influence on performance. These findings indicate that effective leadership combined with high motivation can enhance employee performance within Klinik Utama Mutiara Bandung.